Penurunan Tekanan Darah pada Lansia dengan Senam Ergonomis - Fatsiwi Nunik Andari; Deoni Vioneery; Panzilion Panzilion; Nurhayati Nurhayati; Padila Padila (Journal of Telenursing (JOTING), 2020)
This study aims to determine the influence of ergonomic exercise on reducing blood pressure in the elderly with hypertension at the Center for Sponsorship and Elderly Care. The method used in this research is the quasi-experiment method with one group pre and post-test design. The results of the analysis showed that there were differences in the average systolic blood pressure before and after the ergonomic exercise was 14.00, and the diastolic blood pressure before and after the ergonomic practice was 8.00. Bivariate test results obtained a p-value of 0.00. In conclusion, there is the influence of ergonomic exercise intervention on the reduction of blood pressure in the elderly with hypertension at the Center for Support and Care for the Elderly. Keywords: Hypertension, Elderly, Ergonomic Gymnastics